Establishing radiologic image transmission via a transmission control protocol/Internet protocol network between two teaching hospitals in Houston...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: performance improvement in radiology.' Houston TX, May 6-9, 1999 - Shepherd B (Journal of Digital Imaging)
The technical and management considerations necessary for the establishment of a network link between computed tomography (CT) and magnetic resonance imaging (MRI) networks of two geographically separated teaching hospitals are presented. The University of Texas Medical School at Houston Department of Radiology provides radiology residency training at its primary teaching hospital and at a second county-run hospital located approximately 12 miles away. A direct network link between the two hospitals was desired to permit timely consultative services to residents and professional colleagues. The network link was established by integrating the county hospital free-standing imaging network into the network infrastructure of the Medical School and the main teaching hospital. Technical issues involved in the integration were reassignment of internet protocol (IP) addresses, determination of data transmission protocol compatibilities, proof of connectivity and image transmission, transmission speeds and network loading, and management of the new network. These issues were resolved in a planned stepwise fashion and despite the fact that the system has a rate-limiting T1 segment between the county hospital and the teaching hospital the transmission speed was deemed suitable. The project has proven successful and can provide a guide for planning similar projects elsewhere. It has in fact made possible several new services for the teaching and research activities of the department's faculty and residents, which were not envisaged before the implementation of this connection. Copyright (c) 1999 by W.B. Saunders Company